A Novel Ultra-Wideband Monopole Antenna with Band-Stop Characteristic - Lak, Hadi J.; Ghobadi, Changiz; Nourinia, Javad (Scientific Research Publishing, 2011)
In this letter, a simple monopole antenna with variable band-notched characteristic for ultra wide band (UWB) function is proposed. Two L-shaped quarter-waveguide resonators coupled to the ground plane with two shorting tracks at the sides of the antenna are used to generate stop-band performance around 5.5 GHz (WLAN). The proposed antenna is fabricated on the substrate FR4 (relative permittivity of 4.7) and has a compact size of 16 × 28.5 × 1.6 mm. The designed antenna has a good impedance matching in 3.1 - 11.4 GHz frequency range with VSWR < 2, except the band 5 - 5.85 GHz.
Keywords: Band-Notched Antennas; Band Rejection Antennas; Planar Antennas; Ultra Wideband (UWB)